Development of a Syrian hamster anti-PD-L1 monoclonal antibody enables oncolytic adenoviral immunotherapy modelling in an immunocompetent virus replication permissive setting - Clubb, James H. A.; Kudling, Tatiana V.; Girych, Mykhailo; Haybout, Lyna; Pakola, Santeri; Hamdan, Firas; Cervera-Carrascon, Víctor; Hemmes, Annabrita; Grönberg-Vähä-Koskela, Susanna; Santos, João Manuel; Quixabeira, Dafne C. A.; Basnet, Saru; et al. (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of cancer, but preclinical testing of hypotheses such as combination therapies has been complicated, in part due to species incompatibility issues. For example, one of few permissive animal models for oncolytic adenoviruses is the Syrian hamster, for which an ICI, mainly an anti-PD-L1 monoclonal antibody (mAb) was not previously available. In this study, recombinant Syrian hamster PD-L1 was expressed to develop an anti-PD-L1 mAb using hybridoma technology. Clonal selection through binding and functional studies in vitro, in silico and in vivo identified anti-PD-L1 clone 11B12-1 as the primary mAb candidate for immunotherapy modelling. The oncolytic virus (OV) and ICI combination approach was then evaluated using 11B12-1 and an oncolytic adenovirus encoding tumour necrosis factor alpha (TNFα) and interleukin-2 (IL-2) (Ad5/3-E2F-D24-hTNFα-IRES-hIL-2 or TILT-123). This revealed superior tumour growth control when using the combination therapy versus monotherapies in a Syrian hamster model of pancreatic ductal adenocarcinoma (PDAC). Evaluation of safety and toxicity indicated no significant changes as measured by Syrian hamster serum metabolites, weight and pathological examination. In conclusion, this novel anti-PD-L1 mAb can be used in immunoassays, including immunohistochemistry, flow cytometry, enzyme-linked immunosorbent assay (ELISA) and in vivo to facilitate immunotherapy, immunology, vaccine development, diabetes, atherosclerosis and infectious diseases, including COVID-19 research. We also report cross reactivity of two mAb clones with human PD-L1 highlighting an opportunity for hamster-human cross applications.